Parenting Behaviors And Early Maladaptive Schemas In Low-Income Clinical Population: A Case Study (The Review of Diabetic Studies, 2025)
A number of psychological perspectives place significant emphasis on the role of parenting and parental communication in the development of personality in adulthood. The schema approach is a component of the third-generation therapies, which are characterized by an integrative and holistic approach. Despite the presence of psychosocial risk factors such as poverty, unemployment and insecurity, which are prevalent in the low-income population in the geographical context, family functionality serves as a robust protective factor that fosters healthy personality development and resilience. The objective was to study the parental behaviors perceived during childhood and adolescence in individuals with clinical disorders of limited resources in the City of Poza Rica, Veracruz. Consequently, this study concentrated on the analysis of parental behaviors that occurred during the upbringing of users of a psychological care center coordinated by a public university in this city, applying Young Parenting Inventory (YPI) as the instrument for identifying maladaptive schemas in childhood. The study mainly concludes that mothers are the main source of emotional support and are less likely to foster emotional deprivation. Unpredictable or absent fathers may cause the abandonment pattern. Mistrust is common in unfaithful fathers and manipulative mothers. Maternal overprotection contributes to the vulnerability to harm schema. Lack of resources and parental absence negatively affect children's emotional and psychological development.